Validation of Liquid Chromatographic Method for Analysis of Tacrolimus in a Pharmaceutical Dosage Form - Moyano, Maria Alejandra (2006)
An accurate, simple and reproducible liquid chromatographic method was developed and validated for the determination of  tacrolimus in capsules. The analysis were performed at room temperature on a reverse phase C18 column with UV detection at 210 nm. The mobile phase consisted of  methanol-water (90 + 10) at a constant flow rate of 0.8 mL/min. The method was validated in terms of linearity, precision, accuracy and specificity by forced decomposition of tacrolimus using acid, base, water, hydrogen peroxide, heat and light. The response was linear in the range of 0.09-0.24  mg/mL (r2 = 0.9997). The relative standard deviation values for intra- and interday precision studies were 1.28 and 2.91.  Recoveries ranged between 98.06 and 102.52 %.